New Insights into Xanthophylls and Lipidomic Profile Changes Induced by Glucose Supplementation in the Marine Diatom Nitzschia laevis - Xuemei Mao; Xia Wang; Mengdie Ge; Feng Chen; Bin Liu (Marine Drugs, 2022)
Nitzschia laevis is a candidate microorganism for bioactive compounds (fucoxanthin and eicosapentaenoic acid (EPA)) production. In this study, the impacts of glucose-induced trophic transition on biomass, photosynthesis, pigments, and lipid profiles were examined. The specific growth rate was increased under glucose addition, achieved at 0.47 day−1 (0.26 ± 0.01 day−1 for the group without glucose in medium). However, the photosynthetic parameters and pigments including chlorophylls, fucoxanthin, and diatoxanthin were reduced. The net yield of EPA doubled under glucose addition, reaching 20.36 ± 1.22 mg/L in 4 days. In addition, the alteration in detailed lipid molecular species was demonstrated with a focus on EPA-enriched lipids. The effects of 2-deoxyglucose (2DG) indicated that glucose phosphorylation was involved in glucose-induced regulation. These findings provide novel data for guiding the application of this diatom strain in the functional food industries.